Escalation in asymmetrical relations. A rational strategy for weak states? - Solvang, Øystein (UiT Norges arktiske universitet, 2021)
It is a prevalent view in International Relations scholarship that in conflicts the most powerful party generally prevails. It would follow that weak party escalation usually is an irrational course of action, and therefore should not be attempted. Nonetheless, comparably weak states from time to time escalate confrontations with vastly stronger adversaries, and benefit from it. This paradox is not well understood. While there is a large literature on escalation, it is primarily concerned with situations of symmetrical power. A rare exception is Angstrom and Petersson (2019), who propose that weak party escalation can be rational given specific conditions of the weak state’s preferences, capabilities, or alliances. Asymmetrical conflicts and confrontations of various intensity are numerous, and taking place in politically important regions such as the South China Sea, the Middle East, Eastern Europe, and the Arctic. This paper addresses the knowledge gap surrounding the repeatedly observed, though scarcely understood, phenomenon of weak party escalation. Grounded in offensive realism and theory on strategy of conflict, I aim to answer the research question: how can weak parties in asymmetrical relations use escalation to advance their strategic interests?. Using game theoretical modelling and a case study of the Russo-Norwegian conflict of interest, this paper develops a rigorous explanation for successful weak party escalation. I argue that weak party escalation can be successful given specific conditions of the conflict, such as private information about the cost of conflict, the weak party being supported by a great power ally, or by the weak adopting a limited aims strategy.